A relação professor-aluno: traços culturais presentes na interação em sala de aula - Oliveira, Lúcia Matias da Silva (2009)
This research aims to identify, describe and understand, taking a relational perspective, the elements present in the teacher-student relationship, within a sixth grade classroom of Primary School, from a public school at the city of Barueri/São Paulo, considering the several curricular school subjects. The research proposal is to investigate those elements by means of systematic observation of the classroom routine, in order to notice teachers and students actions and reactions and apprehend what is present in this field of tensions, and also by means of semi-structured interviews with 08 teachers (each one responsible of a different curricular subject) and 31 students. For the data collection, accomplished in 2008 in a public school at the city of Barueri, a protocol of observation and two guidelines of semi-structured interviews (for teachers and students) were built and previously tested. The theoretical support is organized considering mainly the works developed by Charlot, Snyders, Lahire, Pérez-Gómez, Gimeno-Sacristán, Lima and Vinão Frago. The referential research demonstrates that there are few works whose specific proposal is to delineate the elements that compose the teacher-student relationship and the majority of those works considers the first grades of Primary School, what justifies the focus of the present research. This research discusses the teacher-student relationship taking into consideration the dispositions built in the subjects (the teachers and the students ) socialization trajectories, supported by the hypothesis that the investigation of those trajectories allows us to understand the school culture, besides bringing elements that show the interference of this relationship in the hierarchy of the curricular school subjects. The results show a cultural conflict, considered from the subjects social cultural condition and the positions they take facing the different school curricular subjects. The study also reveals that, according to this condition, teachers and students take opposite positions, what reinforces the school failure that is never evaluated considering its causes, but by means of ideologies that consider the cultural aspect as a lack and not as a difference